Bombyx mori monocarboxylate transporter 9 (BmMCT9) is involved in the transport of uric acid in silkworm integument. (13th December 2019) - Wang, Lingyan; Yin, Yaru; Wang, Kun; Cao, Jun; Cheng, Tingcai; Liu, Chun; Zhang, Yan; Zhu, Yong
Abstract: In Bombyx mori, there are more than 30 mutant strains exhibiting the translucent larval skin resulting from a decrease in the uric acid content in epidermal cell. Of these, the Chinese translucent ( oc ) mutant presents a moderately translucent larval skin. Previously, we narrowed the region linked to the oc phenotype to approximately 234 kb by positional cloning, and found that BmMCT9 was severely suppressed in the mutant. Here, we analyzed the mutation and potential molecular function of BmMCT9. Sequence analysis showed that a 2, 624‐bp fragment of BmMCT9 promoter region was replaced by a 22‐bp sequence in the mutant. Luciferase reporter gene assay confirmed that BmMCT9 promoter activity in the mutant was significantly lower than that in the wild type. Knockdown of BmMCT9 caused a translucent phenotype in the first‐instar silkworm larvae. Immunoblotting analysis showed that BmMCT9 expression was severely reduced in the mutant than in the wild type, and immunofluorescence showed that BmMCT9 existed mainly within the cytoplasm of epidermal cells. Together, our results suggest that reduced levels of BmMCT9 were responsible for the translucent phenotype of oc mutant, and that BmMCT9 might function in intracellular vesicles facing the cytoplasm including urate granules in silkworm integument. Abstract : The oc mutant shows a large fragment deletion in BmMCT9 promoter region. BmMCT9 promoter activity in oc was significantly lower than that in wild type. Knockdown of BmMCT9 successfully elicited the translucent larval phenotype.